Improvement of ethylene cracking reaction network with network flow analysis algorithm. (4th August 2016) - Fang, Zhou; Qiu, Tong; Chen, Bingzhen
Highlights: Flow analysis method is applied to reaction network analysis of an industrial ethylene cracking process. Excellent performance on reduction of reaction network enables progress toward decreasing computational scale. The significance of reactions and species is ranked through NFAA in high computational speed. ​ The rankings give guidance on adjusting parameters of ECR network for accurate simulated product prediction. Abstract: Reaction network model is central to ethylene cracking process simulation. Studying an ethylene cracking reaction (ECR) network, which involves hundreds of components and thousands of reactions, becomes a difficult task. To facilitate a rapid and comprehensive reaction network analysis and improve ECR network, this paper introduced a ranking algorithm called network flow analysis algorithm (NFAA) to a reaction network analysis procedure. NFAA analyses the reaction network with comprehensive information such as network topological structure, reaction mechanism, and process model data. Following NFAA, reactions and species are ranked based on their significances. According to the ranking of reactions, unimportant reactions (lower ranking) in ECR network are removed to reduce ECR network complexity and decrease computational scale without loss of prediction accuracy. On the other hand, rankings provide guidance on adjusting parameters of ECR network. The application of NFAA makes a progress in improvement of ECR reaction network in an industrial case.